Competency-based and less time-bound: a new approach to the macro-structure of a medical school curriculum - Miriam Hoffman; Lindsey Dedow; Jeffrey Boscamp (Medical Education Online)
Shifting to a competency-based (CBME) and not time-bound curricular structure is challenging in the undergraduate medical education (UME) setting for a number of reasons. There are few examples of broad scale CBME-driven interventions that make the UME program less time-bound. However, given the range of student ability and varying speed of acquisition of competencies, this is an area in need of focus. This paper describes a model that uses the macro structure of a UME program to make UME curricula less time-bound, and driven more by student competency acquisition and individual student goals. The 3 + 1 curricular model was derived from the mission of the school, and includes a 3-year core curriculum that all students complete and an individualized phase. Students have an 18 month individualized educational program that meets their developmental needs and their educational and professional goals. This is achieved through a highly structured advising system, including the creation of an Individualized Learning Plan, driven by specific goals and targeted Entrustable Professional Activities (EPA). Students who struggle in achieving core competencies can use individualized time to support competency development and EPA acquisition. For students who have mastered core competencies, options include obtaining a masters degree, clinical immersion, research, and community-based experiences. Students can also graduate after the 3-year core curriculum, and enter residency one year early. Structural approaches such as this may contribute to the norming of the developmental nature of medical education, and can advance culture and systems that support CBME implementation at the UME level.